2010
DOI: 10.2337/dc10-0169
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Insulin Aspart With Detemir Does Not Affect Glucose Excursion in Children With Type 1 Diabetes

Abstract: OBJECTIVEWe hypothesized that insulin detemir mixed with aspart had equivalent effects on blood glucose as if being given as separate injections in pediatric type 1 diabetes patients.RESEARCH DESIGN AND METHODSFourteen children with type 1 diabetes were randomly assigned to either Study A (mixed insulins) or Study B (separate insulins) for the first 10 days and crossed over for the last 10 days. Each subject underwent continuous glucose monitoring on the last 72 h of each study.RESULTSThe 48-h area under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The glycemic variability, evaluated in our study by continuous glucose monitoring at baseline (separate) and after 12 wk of treatment (mixed), showed no significant differences between either treatments. These findings were consistent with those observed in earlier works when this variable was evaluated by the same method and same conditions in two short studies – one of 10 d (glargine/lispro or aspart) and one of 20 d (detemir/aspart), separate or mixed in individuals with type 1 diabetes . Nevertheless, it is important to notice that besides CGMS parameters we did not collect data of other glycemic variability markers, which also has been shown to be an independent risk factor for the development of chronic diabetes complications .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The glycemic variability, evaluated in our study by continuous glucose monitoring at baseline (separate) and after 12 wk of treatment (mixed), showed no significant differences between either treatments. These findings were consistent with those observed in earlier works when this variable was evaluated by the same method and same conditions in two short studies – one of 10 d (glargine/lispro or aspart) and one of 20 d (detemir/aspart), separate or mixed in individuals with type 1 diabetes . Nevertheless, it is important to notice that besides CGMS parameters we did not collect data of other glycemic variability markers, which also has been shown to be an independent risk factor for the development of chronic diabetes complications .…”
Section: Discussionsupporting
confidence: 92%
“…A few clinical studies have shown no significant differences in hemoglobin A1c (HbA1c) and glucose variability in patients with type 1 diabetes who mixed a rapid and a long‐acting insulin analog . However, none of them investigated whether mixing a rapid and a long‐acting insulin analog has any deleterious effects on insulins' activity profile.…”
mentioning
confidence: 99%
“…Given the alterations in the time-action profiles observed in our study, we speculate that postdinner hyperglycemia and increased risk of nocturnal hypoglycemia in the study by Nguyen et al (5) were due, at least in part, to the mixed dose of aspart and detemir that was given at dinnertime.…”
Section: Discussionmentioning
confidence: 50%
“…Both the Hvidoere group's and the Fiallo's studies reported on free‐mixed insulin preparations (analog or regular plus NPH or analog plus glargine). In addition of our own study, two papers in the literature tested the pharmacokinetics and short‐term efficacy of analog plus detemir free‐mixing insulin preparations .…”
Section: Discussionmentioning
confidence: 99%